Baptiste. Season two [videorecording (DVD)] - Karyo, Tchéky, 1953-; Shaw, Fiona, 1958-; Hille, Anastasia; Béres, Miklós (PBS Distribution, 2021)
Julien Baptiste delves into Budapest's corrupt underworld to find a British ambassador's family who go missing on a skiing holiday in the Hungarian mountains. Ambassador Emma Chambers is thrust into the crosshairs of Baptiste's most complex case yet, as the detective navigates an untrustworthy Hungarian police force and international media interest as he hunts for her husband and two sons.